Causality between terrorism and FDI in tourism: Evidence from panel data - Maja Nikšić Radić; Daniel Dragičević; Marina Barkiija Sotošek (Economies, 2019)
The aim of this research was to examine the causal link between terrorism and FDI in tourism on the example of a panel of 50 countries for the period from 2000 to 2016. Other control variables were included in order to ensure the validity of the results-number of international tourist arrivals per capita, the KAOPEN index, the KOF Globalisation Index and GDP per capita. The main goal was to look at this issue from the perspective that terrorism does not affect FDI in tourism. The research employed the Granger causality test in a vector autoregressive model (VAR model), the analysis of variance decomposition and the impulse response function within the panel setting. Based on research results, it was found that terrorism does not Granger cause FDI in tourism. The results are in line with recent research related to the subject matter which indicated that the negative effect of terrorism on FDI in tourism was questionable.
Keywords: C33; F21; Z32; 330; FDI in tourism; terrorism; panel Granger causality test; panel VAR analysis